From alienation to industrialisation: hijab activism and the transformation of indonesian urban society from the late 1970s to today - Agus, Setiawan; Achmad, Sunjayadi; Yunadi, Ramlan; Alatas, Alwi (Akademi Pengajian Islam, UM, 2024)
This study aims to analyse the emergence and the dynamic development of hijab activism in Indonesia since the end of the 1970s. The spread of the hijab began with a few Indonesian urban Muslim women who became aware that wearing the hijab is an obligation in Islamic law. They were influenced by a new wave of Islamic da’wah that emerged in the Indonesian urban setting. Initially, the use of the hijab by students in public schools was viewed with suspicion by the Indonesian government and was banned, causing alienation for the wearers. However, the ban was later lifted, and its usage was widely recognised and accepted in the society. The increasing number of Indonesian middle-class Muslim women who wear the hijab has opened up the market for the hijab industry and encouraged producers to be more creative in introducing their newest hijab products. The rise of hijab communities, government support, and the development of online businesses and the international halal industry in recent years have played crucial roles in the rapid expansion of the industry. This study employs a historical method and is supported by a number of primary sources, including interviews with several key players in this field. This research reveals the patterns and phases of hijab transformation over the last four decades, evolving from a symbol of alienation into a lucrative business and industry.